SNP mutations occurring in thyroid hormone receptor influenced individual susceptibility to triiodothyronine: Molecular dynamics and site‐directed mutagenesis approaches. Issue 3 (12th December 2017) - Liu, Yaquan; Qu, Kaili; Hai, Ying; Li, Xin; Zhao, Lei; Zhao, Chunyan
Abstract: The increasing evidences have suggested that expression of single nucleotide polymorphisms (SNP) coded thyroid hormone receptors (THR) generally are associated with individual susceptibility to chemicals. In the present research, multiple molecular dynamics simulations on four SNP mutants (G332R, T337Δ, G345R, and G347E) were performed to investigate the structural and dynamical altering, which could lead to a binding capability variation to triiodothyronine (T3). It proved the structures of two SNP mutants (G345R and T337Δ) occurring in the THR proteins had experienced conformational change to a great extend, which also led to a significant decreasing in binding ability with T3. In addition, two mutates (G345R and G347E) and wild type THR proteins were expressed and purified based on site‐directed mutagenesis technology to test their binding abilities with T3 by fluorescence experiments. The fluorescence quenching efficiencies of two mutates displayed that the conjugation with T3 decreased with a significant rate in G345R system and a little rate in G347E system compared with its wild type. It was consistent with the molecular dynamic research that the SNP mutations did change structures of THR protein, and thereby decreased the binding behavior of T3 at different extent. The overall molecular‐level look at the protein structure may provide the structural basis to explain how one amino acid change can create a ripple effect on the protein structures and eventually affect the binding affinity of the ligands, which maybe the first stage to understand how SNP mutation results in individual difference in susceptibility to variant chemicals. Abstract : (1) Multiple molecular dynamics simulations on four SNP mutants (G332R, T337Δ, G345R, and G347E) proved the structures of two SNP mutants (G345R and T337Δ) occurring in the THR proteins had experienced conformational change to a great extend, which also led to a significant decreasing in binding ability with T3. (2) The fluorescence quenching efficiencies of two mutates (G345R and G347E) displayed that the conjugation with T3 decreased with a significant rate in G345R system and a little rate in G347E system compared with its wild type. (3) The overall molecular‐level look at the protein structure may provide the structural basis to explain how one amino acid change can create a ripple effect on the protein structures and eventually affect the binding affinity of the ligands, which maybe the first stage to understand how SNP mutation results in individual difference in susceptibility to variant chemicals.